AtCSLD3 and GhCSLD3 mediate root growth and cell elongation downstream of the ethylene response pathway in Arabidopsis. (14th December 2017) - Hu, Huizhen; Zhang, Ran; Dong, Shuchao; Li, Ying; Fan, Chunfen; Wang, Yanting; Xia, Tao; Chen, Peng; Wang, Lingqiang; Feng, Shengqiu; Persson, Staffan; Peng, Liangcai
Abstract : CSLD3 overexpression enhances root and hypocotyl growth by increasing cell elongation; CSLD3-mediated hypocotyl elongation is independent of ethylene signaling. Abstract: CSLD3, a gene of the cellulose synthase-like D family, affects root hair elongation, but its interactions with ethylene signaling and phosphate-starvation are poorly understood. Here, we aim to understand the role of CSLD3 in the context of the ethylene signaling and phosphate starvation pathways in Arabidopsis plant growth. Therefore, we performed a comparative analysis of the csld3-1 mutant, CSLD3 -overexpressing lines, and ethylene-response mutants, such as the constitutive ethylene-response mutant i-ctr1 . We found that CSLD3 overexpression enhanced root and hypocotyl growth by increasing cell elongation, and that the root growth was highly sensitive to ethylene treatment (1 µM ACC), in particular under phosphate starvation. However, the CSLD3-mediated hypocotyl elongation occurred independently of the ethylene signaling pathway. Notably, the typical induction of root hair and root elongation by ethylene and phosphate-starvation was completely abolished in the csld3-1 mutant. Furthermore, i-ctr1 csld3-1 double-mutants were hairless like the csld3-1 parent, confirming that CSLD3 acts downstream of the ethylene signaling pathway during root growth. Moreover, the CSLD3 levels positively correlated with cellulose levels, indicating a role of CSLD3 in cellulose synthesis, which may explain the observed growth effects. Our results establish how CSLD3 works in the context of the ethylene signaling and phosphate-starvation pathways during root hair growth, cell elongation, and cell wall biosynthesis.